2017
DOI: 10.1002/clc.22762
|View full text |Cite
|
Sign up to set email alerts
|

Changes in parameters of right ventricular function with cardiac resynchronization therapy

Abstract: Background Studies have shown that cardiac resynchronization therapy (CRT) significantly improves right ventricle (RV) size and function in patients with heart failure (HF). Hypothesis CRT does not lead to improvement in RV function independent of baseline clinical variables. Methods A systematic search of studies published between 1966 to August 31, 2015 was conducted using Pub Med, CINAHL, Cochrane CENTRAL and the Web of Science databases. Studies reporting tricuspid annular plane systolic excursion (TAPSE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…Possible mechanisms of the negative effect of enlarged right parts of the heart are the increase in stagnation, reduction of renal blood flow, with the subsequent development of renal dysfunction. In connection with CRT in patients of group 1 echocardiographic parameters improved not only in the left but also in the right parts of the heart, confirming the literature data on the ability of CRT to cause favorable RV remodeling [15].…”
Section: Discussionsupporting
confidence: 82%
“…Possible mechanisms of the negative effect of enlarged right parts of the heart are the increase in stagnation, reduction of renal blood flow, with the subsequent development of renal dysfunction. In connection with CRT in patients of group 1 echocardiographic parameters improved not only in the left but also in the right parts of the heart, confirming the literature data on the ability of CRT to cause favorable RV remodeling [15].…”
Section: Discussionsupporting
confidence: 82%
“…There are several studies that demonstrate a positive effect of LV CRT on the RV function, indicating the dependence of both ventricles in biventricular circulation. 6 In short, the presented case emphasizes the need for further studies to evaluate the relevance of RV CRT in patients with RBBB after cardiac surgery and reduced RV function. In particular, prospective, multicentric studies are needed to evaluate long-term outcomes and define the indications and patient selection criteria for a long-term RV CRT.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, the higher likelihood of having a decrease in SII values during 6-month CRT in our patients with higher baseline QRS seems notable given the role of morphology of QRS waves in deciding ventricular dyssynchrony for CRT inclusion criteria as well as the consideration of a strong positive correlation between the larger QRS area in the pre-treatment period with better CRT response [11]. Besides its well-known effects on LV function (i.e., improved LVEF, decreased intraventricular mechanical dyssynchrony, and favorable LV remodeling) [27,28], some studies have also suggested the association of CRT with significant improvements in RV size and function in patients with HF [29][30][31][32]. In the current study, apart from achievement of CRT response (based on EF, LVESV and NYHA) in at least 60% of patients, SII change during CRT was also correlated with echocardiographic parameters of RV function (negatively with TAPSE and RV FAC, and positively with RVES area and RVED area).…”
Section: Discussionmentioning
confidence: 99%